Molecular Characterization of a Novel Integrative Conjugative Element ICEHpa1 in Haemophilus parasuis - Sun, Hua-Run; Cui, Xiao-Die; Liu, Xiao-Kang; Li, Shuai-Hua; Yi, Kai-Fang; Pan, Yu-Shan; Wu, Hua; Yuan, Li; Hu, Gong-Zheng; He, Dan-Dan (Frontiers in Microbiology, 2020)
ICEHpa1 was identified in the genome of a serovar 8 Haemophilus parasuis ST288 isolate YHP170504 from a case of swine lower respiratory tract infection. The aim of the present study was to characterize the integrative conjugative element ICEHpa1 and its multiresistance region. Susceptibility testing was determined by broth microdilution and the complete ICEHpa1 was identified by WGS analysis. The full sequence of ICEHpa1 was analysed with bioinformatic tools. The presence of ICEHpa1, its circular intermediate and integration site were confirmed by PCR and sequence analysis. Transfer of ICEHpa1 was confirmed by conjugation. ICEHpa1 has a size of 68,922 bp with 37.42% GC content and harbours 81 genes responsible for replication and stabilization, transfer, integration and accessory functions, as well as seven different resistance genes (blaRob-3, tet(B), aphA1, strA, strB, aac(6)'-Ie-aph(2')-Ia and sul2). Conjugation experiments showed that ICEHpa1 could be transferred to H. parasuis V43 with frequencies of 6.1×10-6. This is the first time a multidrug-resistance ICE has been reported in H. parasuis. Seven different resistance genes were located on a novel integrative conjugative element ICEHpa1, which suggests that the ICEHpa1 is capable of acquiring foreign genes and serving as a carrier for various resistance genes.